Ultra-fast fabrication of bulk ZrNiSn thermoelectric material through self-propagating high-temperature synthesis combined with in-situ quick pressing. (May 2019) - Hu, Tiezheng; Cao, Weiqiang; Yang, Dongwang; Yan, Yonggao; Cao, Yu; Zhang, Tingting; Su, Xianli; Liu, Wei; Poudeu-Poudeu, Pierre; Tang, Xinfeng
Abstract: The conventional fabrication of bulk thermoelectric materials usually involves time and energy consuming steps including melting, annealing and sintering et al, which restricts the large-scale application. Herein, high thermoelectric performance ZrNiSn bulks were synthesized by one step self-propagating high-temperature synthesis combining with in-situ quick pressing (SHS-QP). The correlation among SHS process, QP process and the critical pressure, is systematically investigated. The reduced grain size due to non-equilibrium feature of SHS-QP leads to a significant reduction in the thermal conductivity and a high figure of merit ZT 0.7. Graphical abstract: Unlabelled Image